Land suitability for endemic plants in Kiara Payung Biodiversity Park, West Java - TINA SAFARIA NILAWATI; WAHYU SURAKUSUMAH; VITA ANNISYA (Nusantara Bioscience, 2015)
Abstract. Nilawati TS, Surakusumah W, Annisya V. 2015. Land suitability for endemic plants in Kiara Payung Biodiversity Park, West Java. Nusantara Bioscience 7: 112-117. According to Bappenas data (2003), there are 38.000 species of plants, 55% of which are endemic, in Indonesia. However, in Indonesia, there is severe environmental deterioration which may cause extinction of endemic plants. One way to solve the environmental degradation is by conducting ex situ conservation, such as the establishment of Kiara Payung Biodiversity Park in Sumedang, West Java, Indonesia. The aim of this research was to determine land suitability of the park for plantation of endemic plants of West Java, Bouea macrophylla, Blumeodendron tokbrai, and Pterospermum javanicum, based on climatic and edaphic factors using GIS Arcview software. The climatic and edaphic data were taken from the field, and then they were overlaid in land unit maps with other parameters of every endemic plant species in West Java based on literature review. All data were interpreted based on land evaluation method by matching process. The results showed that the endemic plants B. macrophylla and P. javanicum are not suitable to be planted in Kiara Payung Biodiversity Park, while B. tokbrai is suitable to be planted in the entire blocks 5, 6, and 7 and part of blocks 2,3,4 and 8 of this park.